Pengaruh Pembelajaran Online terhadap Hasil Belajar Taruna Diploma III Teknik Bangunan dan Landasan Angkatan 4A dan 4B Semester II di Politeknik Penerbangan Surabaya - Bambang Wasito (Jurnal Penelitian)
The purpose of e-learning is to increase the students' absorption of the material being taught, increase the active participation of students, improve their independent study skills, and improve the quality of learning materials. It is hoped that it can stimulate the growth of new students' innovations in accordance with their respective fields.In the midst of the Covid-19 pandemic, our education system must be ready to take the leap to transform online learning for all students / students / cadets and by all teachers and lecturers.Whereas all question items have a significance value of less than 0.05, so it is said that all questions posed to respondents are valid.The calculation results in the SPSS appendix show that the Cronbach's Alpha value is 0.917. This value is above 0.6, it can be said that the questionnaire in this study is reliable.The value of the correlation coefficient (R) is 0.975 or close to 1. This means that the relationship between the independent variables of online learning (X) and learning outcomes (Y) Cadets Diploma III of Building and Foundation Engineering Class 4A and 4B Semester II at Aviation Polytechnic of Surabaya is strong in the direction of . This means that if the free online learning variable (X) is increased, the dependent variable, namely the learning outcomes (Y) of the Cadets Diploma III in Building and Platform Engineering Class 4A and 4B Semester II at Aviation Polytechnic of Surabaya will also increase, and vice versa. The percentage of the influence of the independent variable on the dependent variable as shown by the coefficient of determination simultaneously (Rsquared¬) is 0.975 or 97.5%. This means that the ups and downs of the dependent variable, namely the learning outcomes (Y) of Cadets Diploma III in Building and Platform Engineering Class 4A and 4B Semester II at Aviation Polytechnic of Surabaya are influenced by free online learning (X) of 97.5% and the remaining 2.5 % influenced by other variables outside of this studyFor the free online learning variable (X), the t value obtained is 15.269 and the significance value is 0.000, this value is smaller than a = 0,05 so it means that the free online learning variable (X) has a significant effect on dependent variable learning outcomes (Y) Cadets Diploma III Building and Platform Engineering Batch 4A and 4B Semester II at Aviation Polytechnic of Surabaya